Outcomes of salvage therapy for steroid‐refractory acute severe ulcerative colitis: ciclosporin vs. infliximab. Issue 3 (20th June 2013) - Croft, A.; Walsh, A.; Doecke, J.; Cooley, R.; Howlett, M.; Radford‐Smith, G.
Summary Background Up to 40% of patients who present with acute severe ulcerative colitis (UC) fail to make an adequate response to intravenous corticosteroids. Ciclosporin or infliximab are currently employed as salvage therapy in this clinical scenario. Aim To compare clinical outcomes in patients treated with ciclosporin or infliximab in the setting of steroid‐refractory acute severe UC. Methods A prospective study of 83 consecutive presentations of steroid‐refractory acute severe UC from 1999 to 2009 was conducted. All study participants satisfied the Truelove and Witts' criteria for acute severe UC. The primary outcome measures were rates of colectomy at discharge from hospital and at 3 months and 12 months following admission. Results Eighty‐three steroid‐refractory acute severe UC events were generated by 83 patients. Salvage therapy was instituted with ciclosporin in 45 patients and infliximab in the remaining 38 patients. Of those patients who received ≥72 h of ciclosporin (2–4 mg/kg), 56% (24/43) avoided colectomy at the time of discharge, while this figure was 84% (32/38) for those administered one dose of infliximab (5 mg/kg) (P = 0.006). At 3 months, the colectomy‐free rate was 53% for ciclosporin (23/43) vs. 76% for infliximab (28/37) (P = 0.04), and 42% (18/43) vs. 65% (24/37) at 12 months (P = 0.04). There were no deaths and two serious adverse events, both occurring in the ciclosporin group. Conclusions In this large cohort of patients presenting with acute severe UC, we have observed that infliximab salvage therapy is associated with lower rates of both severe adverse events and colectomy than ciclosporin in the short‐term and medium‐term.